Isolation of high-amylase Rhizopus arrhizus from Vietnamese ‘Banh men’ for efficient hydrolysis of glutinous rice (Oryza sativa var. glutinosa) - Vo, Phuong-Mai; Nguyen, Duy-Tan; Nguyen, Huu-Thanh; Nguyen, Phu-Tho (Agriculture and Natural Resources, 2025)
Importance of the work: Traditional fermented starters, such as ‘Banh men’, used in the production of Vietnamese sweet-fermented rice are valuable sources of microbial diversity with industrial potential. Identifying efficient amylase-producing molds from these starters can enhance starch-based bioprocessing, while preserving traditional fermentation knowledge. Objectives: To isolate and characterize amylase-producing molds from Vietnamese Banh men, assess their enzymatic activity and investigate their ability to hydrolyze glutinous rice into fermentable sugars. Materials and Methods: A sample of 14 mold strains was isolated from Banh men and screened for amylase activity on starch agar. Top producers were identified morphologically and via internal transcribed spacer sequencing. Selected strains were cultivated in glutinous rice, with hydrolysis monitored based on the extract yield, Brix value and sugar content (dinitrosalicylic acid method). Results: Dominant isolates belonged to the Mucor and Rhizopus genera (70% prevalence). The strains BMTS1 and BMCP2.3 (both Rhizopus arrhizus) had the highest amylase activity (2.94 U/mL and 2.60 U/mL, respectively) and starch degradation indices (>95%). During rice hydrolysis, both strains produced approximately 100 mL of extract after 72 hr, with reducing sugars increasing from 6.38 mg/mL to 37.49 mg/mL and polysaccharides declining by 89%. Main finding: R. arrhizus BMTS1 and BMCP2.3 from Banh men are potent starch hydrolyzing agents, offering a sustainable solution for converting glutinous rice into sugar-rich substrates for food and beverage applications.